Sural neuro-cutaneous flap in the management of foot and ankle soft tissue defects in a diabetic population - Assi, Chahine (2016)
• Background: Soft tissue defects in the foot and ankle region are challenging conditions particularly in diabetic patients. We evaluated the reliability of the sural flap in treating such defects among a diabetic population. Material and Methods: This is a continuous retrospective series of 14 patients with type 2 diabetes treated with an ipsilateral sural flap for soft tissue defects around the rear foot (11 cases) and over the malleolar areas (3 cases). Three patients had an open tibia fracture (Gustillo IIIb), four had chronic osteitis and seven had a chronic heel ulcer. Results : The mean follow-up at 28 months showed healing of the flap at a mean of 24 days, donor site healing in two weeks, one case of total flap necrosis, three cases of skin edge necrosis, two cases of temporary venous congestion and 10 cases of hypoesthesia of the lateral border of the foot. No infection or recurrence of infection was encountered. Conclusion : We found the sural flap useful, reproducible and reliable in treating soft tissue defects in diabetic patients with a low frequency of serious complications.